Digital Workplace Adaptation: A Comparative Analysis Of The Effects Of Workload And Innovation On The Performance Of Millennial vs. Non-Millennial Employees - Isnaidi, Isnaidi; Purwati, Astri Ayu; Hafni, Layla (International Journal of Economics Development Research (IJEDR), 2025)
This study investigates the impact of digital workload on employee performance, mediated by employee loyalty and moderated by individual innovation behavior, with a generational perspective distinguishing between millennial and non-millennial employees. Utilizing a quantitative explanatory approach, data were collected via total sampling of 52 BAPPEDA employees and analyzed through Structural Equation Modeling using Partial Least Squares (SEM-PLS) and Multi-Group Analysis (MGA). Findings reveal that digital workload negatively affects performance, particularly among non-millennials, while employee loyalty and innovation behavior positively influence performance. Digital adaptation acts as a crucial moderator, buffering the adverse effects of digital workload and enhancing the positive impact of innovation. The study underscores the importance of digital literacy, innovation culture, and tailored generational strategies to optimize employee performance in digitizing public institutions.